FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL BELAJAR AKUNTANSI KEUANGAN MENENGAH - Adri Eko Prabowo (Universitas Negeri Malang, 2014)
This research is designed to analyze the indirect influences of learning orientation, interaction among students, intensity of accessing social media and technical ability toward learning outcome of intermediate financial accounting through learning motivation as mediating variable on students of FKIP Universitas Islam Riau. In analyzing the mediator variable (learning motivation), Sobel Test is applied. Meanwhile, direct influence toward learning motivation and learning outcome is analyzed using SEM. The findings in this research are showing that 1) learning orientation, interaction among students, intensity of accessing social media and technical ability influence directly to the learning motivation; 2) there is no direct influences of learning orientation, interaction among students, intensity of accessing social media and technical ability to the learning outcome; 3) learning motivation influence directly to the learning outcomer; 4) learning orientation, interaction among students, intensity of accessing social media and technical ability influence indirectly to the learning outcome through the learning motivation.